Preoperative external beam radiotherapy and reduced dose brachytherapy for carcinoma of the cervix: survival and pathological response - Jacinto, Alexandre A (BioMed Central, 2007)
PURPOSE: To evaluate the pathologic response of cervical carcinoma to external beam radiotherapy (EBRT) and high dose rate brachytherapy (HDRB) and outcome. MATERIALS AND METHODS: Between 1992 and 2001, 67 patients with cervical carcinoma were submitted to preoperative radiotherapy. Sixty-five patients were stage IIb. Preoperative treatment included 45 Gy EBRT and 12 Gy HDRB. Patients were submitted to surgery after a mean time of 82 days. Lymphadenectomy was performed in 81% of patients. Eleven patients with residual cervix residual disease on pathological specimen were submitted to 2 additional insertions of HDRB. RESULTS: median follow up was 72 months. Five-year cause specific survival was 75%, overall survival 65%, local control 95%. Complete pelvic pathological response was seen in 40%. Surgery performed later than 80 days was associated with pathological response. Pelvic nodal involvement was found in 12%. Complete pelvic pathological response and negative lymphnodes were associated with better outcome (p = .03 and p = .005). Late grade 3 and 4 urinary and intestinal adverse effects were seen in 12 and 2% of patients. CONCLUSION: Time allowed between RT and surgery correlated with pathological response. Pelvic pathological response was associated with improved outcome. Postoperative additional HDRB did not improve therapeutic results. Treatment was well tolerated.